Penerapan TPACK dalam Pembelajaran Bahasa Indonesia Berdasarkan Kurikulum Merdeka Kelas X di SMA Negeri Kota Bengkulu - Prihandini, Renata; Kurniawan, Rio; Yanti, Nafri (Jurnal Korpus, 2025)
The implementation of TPACK (Technology Pedagogical Content Knowledge), which combines technology, pedagogy and content knowledge, is considered the right solution to bridge the gap between technological developments and effective learning methods. The aim of this research is to describe the practice of implementing Indonesian language learning using the TPACK (Technology Pedagogical Content Knowledge) Framework based on the Merdeka Curriculum for class X at Bengkulu City State High School. In this research, the research method used is descriptive qualitative research methods. Data collection techniques in this research were carried out by means of classroom observations, interviews with teachers, and video recordings. The data analysis technique is carried out by means of data reduction, namely sorting relevant observation and interview data, data presentation, namely presenting the results of data reduction in the form of a short research on the implementation of Indonesian language learning using TPACK (Technology Pedagogical Content Knowledge) based on the Merdeka Curriculum for class and learning methods that involve students actively, teachers are clear in collecting and assessing student assignments, teachers are active, communicative and organized in class management, teachers understand the material being presented, teachers are clear in explaining the material and always involve students actively in explaining the material.